AN OVERVIEW VAPE USE IN TERMS OF LIFESTYLE IN TEENAGER - Mokhtar Jamil; Ratna Roesardhyati; Ana Masrurotul Jannah; Tien Aminah; Maulana Arif Murtadho (Program Studi Keperawatan, Fakultas Ilmu Kesehatan, ITSK RS dr Soepraoen, 2024)
The number of teenage vape users in Indonesia is currently increasing. Vape is indeed a modern lifestyle among the people. The development of lifestyle can be feared because it can make a person consume goods that are not concerned with the function of these goods but only to fulfill their desires. The purpose of this study was to describe the factors underlying the use of vape in terms of the lifestyle of students at SMPN 1 Kepanjen. The research design is descriptive. The population of this study was all 40 students of SMPN 1 Kepanjen who used vape. The sampling technique used is total sampling. The variables studied are the factors underlying the use of vape in terms of lifestyle. The research results were analyzed using univariate analysis. The research instrument used a questionnaire in the form of a google form. This research was conducted on 7 – 27 July 2023. The results of the study showed that most of them had a background of 16 people (60%), almost half of them did not have a background of 14 people (40%). From these results it can be concluded that age, gender, weekly allowance, have you ever received information about vape, sources of information, intensity of using vape, duration of using vape Based on this research, it is hoped that it can increase the role of educational institutions, especially regarding vape use by providing counseling to students about the dangers of vape use and as a self- evaluation of students about vape use so that it can encourage students to seek positive coping mechanisms by carrying out positive activities to reduce smoking. vaping use.